Sex differences in ventricular arrhythmia, atrial fibrillation and atrioventricular block complicating acute myocardial infarction - Alnsasra, Hilmi; Tsaban, Gal; Weinstein, Jean Marc; Nasasra, Mhamad; Ovdat, Tal; Beigel, Roy; Orvin, Katia; Haim, Moti (Frontiers in Cardiovascular Medicine, 2023)
Background: Acute myocardial infarction (AMI) complicated by tachyarrhythmias or high-grade atrioventricular block (HAVB) may lead to increased mortality.To evaluate the sex differences in patients with AMI complicated by tachyarrhythmias and HAVB and their associated outcomes.We analyzed the incidence rates of arrhythmias following AMI from the Acute Coronary Syndrome Israeli Survey database from 2000 to 2018. We assessed the differences in arrhythmias incidence and the associated mortality risk between men and women.Results: This cohort of 14280 consecutive patients included 3159 (22.1%) women and 11121 (77.9%) men. Women were less likely to experience early ventricular tachyarrhythmia (VTA),(1.6% vs 2.3%, p=0.034), but had similar rates of late VTA (2.3% vs. 2.2%, p= 0.62). Women were more likely to experience atrial fibrillation (AF) (8.6% vs 5.0%, p<0.001) and HAVB (3.7% vs 2.3%, p<0.001). The risk of early VTAs was similar in men and women (adjusted Odds Ratio (aOR) = 0.76, p=0.09), but women had a higher risk of AF (aOR =1.27, p=0.004) and HAVB (aOR =1.30, p=0.03). Early [adjusted hazard ratio (aHR)=2.84, p<0.001] and late VTA (aHR=4.59, p<0.001), AF (aHR=1.52, p<0.001) and HAVB (aHR=2.83, p<0.001) were associated with increased 30-day mortality. Only late VTA (aHR=2.14, p<0.001) and AF (aHR=1.44, p=0.002) remained significant in the post 30 days period.During AMI women experienced more AF and HAVB but fewer early VTAs than men. Early and late VTAs, AF, and HAVB were associated with increased 30-day mortality. Only late VTA and AF were associated with increased post-30-day mortality.